Kriminalisasi dan Reformulasi Perbuatan Prostitusi dalam Hukum Pidana: Catatan Kritis atas Minimnya Pengaturan Perbuatan Prostitusi Di Indonesia - Amrianto, Andika Dwi; Putri, Maria Kunti Atika; Yusup, Ahmad; Putra, I Putu Aditya Darma (Universitas Muhammadiyah Yogyakarta, 2023)
The practice of prostitution, which grew rapidly and massively through electronic means of information dissemination, impacted various groups. The worst impact of the massive practice of prostitution was the spread of sexually transmitted diseases, which adversely affect the health of both individuals directly involved in prostitution and those whose partners engage in such activities. This study aims to find out the regulation of prostitution within the current Indonesian criminal law and to provide an overview for legislators in the formation of prostitution regulations in the future. Furthermore, it needs to elucidate the reasons behind the necessity of regulating prostitution in Indonesia. The research method employed was legal research of a normative type. This research using secondary data obtained through library research and studies of laws and regulations. The analytical method used in this study was a prescriptive analytical technique. The results of this study revealed that currently there were no regulations governing the practice of prostitution in Indonesia rigidly and clearly. Therefore, it is necessary to criminalize and reformulate the offense of prostitution in Indonesian Criminal Law to avoid the effects arising from the act of prostitution that cause potential victims due to the spread of sexually transmitted diseases.